An Analysis of Crohn’s Disease Activity Indices from a Registry of Patients in Eastern Pennsylvania - JF Reed; Linda A Faust (Canadian Journal of Gastroenterology)
The objectives of this report were to compare Crohn’s disease patients’ assessment of disease activity and its effect on their well-being to their physician’s assessment of the disease activity and the patient’s well-being; and to use existing Crohn’s disease indices in comparing the severity of Crohn’s disease across various indices. The indices included in this study were the National Cooperative Crohn’s Disease Study index, the Harvey and Bradshaw Index, the Oxford Index, the Modified Organisation Mondiale de Gastroentérologie Index, the Cape Town Index, the Bristol Index, and the St Marks Index. The comparison of Crohn’s disease patient self-evaluation and physician evaluation of the patient indicates a significant agreement between patient and physician assessment of disease activity (Χ2 41.68, P=0.00001). Cohen’s weighted kappa, a chance-corrected coefficient of agreement for nominal scales, was also used to evaluate the quality of agreement between physician and patient assessment of well-being. The weighted kappa (0.2322, P=0.0002) indicates a significant level of agreement.